2019
DOI: 10.1177/1464884919832188
|View full text |Cite
|
Sign up to set email alerts
|

Navigating conflicts of interest: Ethical policies of 12 exemplary Asian media organisations

Abstract: While research into non-Western media systems and professional norms are growth areas in journalism studies, little is known about the policies of news organisations beyond a few celebrated global brands. This exploratory study is situated in that gap. It examines 12 reputable media organisations in seven territories -China, India, Indonesia, Malaysia, Pakistan, Philippines and Taiwan. Through interviews with top-level editors and executives, the study analyses their stated policies with regard to commercial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Similarly, a study by Neilson and Gibson (2022) showed that audience engagement editors defined their roles as simply the pursuit of an audience for their publication. Though many of the respondents are willing to acknowledge the influence of economic consideration in the articulation of their roles, the blurring line between the editorial department and that of business in several newsrooms (George, Zeng & Mazumdar, 2021;Bogart, 2017;Carlson, 2015) makes this effort unsustainable. An empirical study has shown that audience engagement is a priority if it is central to their business model (Lawrence, Radcliffe & Schmidt, 2018).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Similarly, a study by Neilson and Gibson (2022) showed that audience engagement editors defined their roles as simply the pursuit of an audience for their publication. Though many of the respondents are willing to acknowledge the influence of economic consideration in the articulation of their roles, the blurring line between the editorial department and that of business in several newsrooms (George, Zeng & Mazumdar, 2021;Bogart, 2017;Carlson, 2015) makes this effort unsustainable. An empirical study has shown that audience engagement is a priority if it is central to their business model (Lawrence, Radcliffe & Schmidt, 2018).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The Sarkar family, which co-founded the Bengali newspaper ABP in 1922, had strong links with Bengal's literary and cultural world (Mukherjee, 2012). Dailies such as the English language The Hindu, influential in southern states and reputed for editorial standards, and ABP had the tradition of family owners serving as chief editors (George et al, 2019;Ninan, 2013). In a significant break of tradition, ABP hired a professional editor in 2016 after proprietor Aveek Sarkar, who edited ABP since the mid-1980s, stepped down.…”
Section: Proprietorial Values Politics and Corporate Logicmentioning
confidence: 99%
“…In a significant break of tradition, ABP hired a professional editor in 2016 after proprietor Aveek Sarkar, who edited ABP since the mid-1980s, stepped down. While family owners may turn newspapers to any direction, they could be credited with protecting editorial integrity and professionalism if the family places a high stake on the reputation of the news organization; the family owners of The Philippine Daily Inquirer are known to have upheld such a tradition in Asia among others (George et al, 2019). Proprietors may 'publish news or views with a potentially high economic or political downside' for the organization as a form of 'public service commitment' (Benson, 2016, p. 31).…”
Section: Proprietorial Values Politics and Corporate Logicmentioning
confidence: 99%
See 1 more Smart Citation